Legal Protection Of The Rights Of Children As Victims Of Copulation In The Perspective Of Victimology - Novita Rahmaini Tumanggor; Edy Warman; Muhammad Hamdan; Edy Ikhsan (International Asia Of Law and Money Laundering, 2022)
The results of the research conducted, it can be concluded as follows: First, the Book of the law of Criminal Law (PENAL code), in particular if it is done against children is regulated in Law Number 35 of 2014 concerning amendment to Law Number 23 Year 2002 About Child Protection as well as if committed against a person who is still included in the family relations regulated in Law Number 23 Year 2004 On the Elimination of Violence In the Household. Second, the Factors that cause the onset of criminal information against children, namely Internal Factors (psychological factors, biological factors and moral factors) and External Factors (socio-cultural factors, economic factors and the factor of the mass media). Third, the protection provided Law Number 35 Year 2014 which refers to Article 81 paragraph (2) by providing sanctions and penalties to the perpetrators of criminal acts of intercourse to the child and to the child is given the protection of which is entitled to rehabilitation from the government both physically and mentally, spiritually and socially, in addition to it its privacy required to be protected.